Quality management in the activities of enterprises of oil and gas sector of Ukraine - Мельницький, М. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article is concerned with the study of basic features of quality formation in the process of gas and oil complex activity in Ukraine and its allotted subjects of management. Basic factors which influence the quality are identified, types of gas and oil industry activity are considered, the scheme to transform quality into a competitive factor is introduced. The "UKRNAFTA" activity is investigated in terms of works and services quality where an important place is occupied by mining boreholes constructions.